An Evaluation of Veterinary Production and Services in Bangladesh - Prova, Tonema Tabassum; Rahman, Md. Hasanur (Society & Sustainability, 2021)
As a developing country, the economy of Bangladesh is based on agricultural activities. Veterinary science and production have a significant impact on the socio-economic development of the country. The current study evaluates the sector in terms of Animal Feeds, Disease and Diagnostic Services, Preventive Veterinary Service, Clinical Service, Artificial Insemination, Wildlife Healthcare, Administrative Assistance, Legal framework and policy regime, Veterinary Public Health and Zoonoses, Research and Development for Veterinary Science, Licensing Veterinary Activities, Industrial Evaluation Based on ventures, and Veterinary education and research activities. Veterinary activities and economic development are positively correlated and affect poverty alleviation. The current study is a pioneering attempt to evaluate the area in the context of Bangladesh, which will essentially add value to the existing literature.